Implementation of Teacher Working Group Development in Improving the Quality of the Learning Process (A Case Study of Elementary School Teachers in Bougenvile Cluster 5 Ulubelu District) - Win Fransiska; Juhri Abdul Mu'in; Fatqul Hajar Aswad (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This study aims to describe and analyze the implementation of KKG development in improving the quality of the learning process, the supporting and inhibiting factors in its implementation, as well as its impact on teacher professionalism in Bougenvile 5 Cluster, Ulubelu District.This study employed a qualitative approach using a case study method. The research subjects consisted of KKG administrators, elementary school teachers, and school principals in Bougenvile 5 Cluster, Ulubelu District. Data were collected through in-depth interviews, observation, and analysis of relevant school records. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data credibility was ensured through source and technique triangulation.The results indicate that the implementation of KKG development in Bougenvile 5 Cluster has been carried out through various programs, including regular meetings, instructional training, pedagogical discussions, and collaborative preparation of learning tools. KKG development contributes positively to improving the quality of the learning process, particularly in lesson planning, the use of varied teaching methods, and increased student participation and engagement. The main supporting factors include teacher commitment, principal support, and educational policies, while the inhibiting factors include limited time, inadequate facilities, and inconsistency in teacher attendance. This study concludes that systematically and sustainably managed KKG development is able to improve the quality of the learning process in elementary schools. Key Words: Teacher Working Group, learning process quality, teacher professional development.